Berberis microphylla: A species with phenotypic plasticity in different climatic conditions - Radice, Silvia (2018)
Berberis microphylla G. Forst., commonly called as "calafate" produces small fruits with high content of carbohydrates, phenols and antioxidants. The objective of this work was to characterize the vegetative and reproductive cycle of Berberis microphylla cultivated on Moreno (Buenos Aires province), Argentina in comparison with the results obtained in Ushuaia (Tierra del Fuego) which is its place of origin. Vegetative growth was very different in the two localities. Moreno plants grew with more lax branches than Ushuaia. In effect, length of the shoots was significantly higher for Moreno than Ushuaia plants. Flowering period in Ushuaia plants was concentrated in November while in Moreno it happens earlier and over a longer period. Pollen grains collected from Moreno flowers had a diameter of ~60 μm, significantly different to pollen grain from Ushuaia (57.11 μm). Nevertheless, pollen grain vitality was superior in Ushuaia flowers (75%) as compared to Moreno flowers (52%). On the other hand, fruit harvested in Moreno was at 60 days from full bloom while in Ushuaia plants at 120 days. Although the size and compounds measured in the fruits of Moreno were lower than those of Ushuaia, results obtained indicate that B. microphylla grown on Moreno is an interesting option to obtain another nutraceutical fruit near the centers of mass consumption.